L’arte e il perturbante. Un nuovo libro ne analizza la relazione: Mario Rivardo-Maddalena Muzio Treccani, Le vicissitudini del perturbante nell’arte e in psicoanalisi. Felix Vallotton e Francis Bacon, Milano, Scalpendi Editore, 2024. (Materiali di Estetica. Terza serie, 2024)
In his review of "Le vicissitudini del perturbante nell’arte e in psicoanalisi" by Mario Rivardo and Maddalena Muzio Treccani, the author examines the exploration of the uncanny in the art of Felix Vallotton and Francis Bacon. The book utilizes a Freudian perspective to analyze how these artists invoke the uncanny through their distinct but thematically connected works. Vallotton's introspective and somber scenes contrast with Bacon's visceral distortions of the human form, each artist effectively unsettling the viewer. The author underlines the thorough psychological and biographical context the authors provide, enhancing the understanding of how the uncanny not only influences artistic expression but also shapes viewer reception.
Keywords: book review; uncanny; art; Psychoanalysis; Felix Vallotton; Francis Bacon